Inclusion of the insecticide fenitrothion in dimethylated-β-cyclodextrin: unusual guest disorder in the solid state and efficient retardation of the hydrolysis rate of the complexed guest in alkaline solution - Cruickshank, Dyanne L.; Rougier, Natalia M.; Vico, Raquel V.; Bourne, Susan A.; Buján, Elba I.; Caira, Mino R.; de Rossi, Rita H. (Beilstein Journal of Organic Chemistry, 2013)
An anhydrous 1:1 crystalline inclusion complex between the organophosphorus insecticide fenitrothion [O,O-dimethyl O-(3-methyl-4-nitrophenyl)phosphorothioate] and the host compound heptakis(2,6-di-O-methyl)-β-cyclodextrin (DIMEB) was prepared and its structure elucidated by single-crystal X-ray diffraction. This revealed two independent host molecules in the asymmetric unit. In one of these, the cavity is occupied by two disordered guest components (distinguishable as rotamers with respect to the P–OAr bond) while in the other, three distinct guest components with site-occupancies 0.44, 0.29 and 0.27 appear, the last having a reversed orientation relative to all the other components. Kinetic studies of the alkaline hydrolysis of fenitrothion in the presence of DIMEB showed a remarkable reduction of 84% in the rate of this reaction relative to that for the free substrate, a value exceeding those previously attained with the native hosts, β- and γ-cyclodextrin, and fully methylated β-cyclodextrin.
Keywords: crystal structure; cyclodextrin; fenitrothion; hydrolysis; inclusion complex